Examining factors affecting participation of local SMEs in export markets, A case study Clothing and Food Processing. - Dalali, Kelvin. (Mzumbe University, 2026)
A dissertation submitted in partial fulfillment of the requirement for the degree of Master of Business Administration in Corporate Management of Mzumbe University